Effect of pattern recognition ability training on judging performance of Malaysian rhythmic gymnastics judges - Teh, Lah Hoong (2010)
Studies have shown that expert judges are typically very accurate in their evaluations as compared to non-experts. Although the judging task challenges the limited capacities of attention, memory and speed of processing of judges that are characteristic of humans, expert judges have learned to circumvent processing limitations encountered by novice judges by acquiring certain cognitive structures. One possible acquisition from the repeated judging tasks could be an improvement in the pattern recognition skills. This research examined the significance of pattern recognition ability in the judging performance of Malaysian rhythmic gymnastics judges who were correspondingly classified by the Malaysian Gymnastics Federation as expert, non-expert and novice. In the first study, thirty participants categorised by the Malaysian Gymnastics Federation were subjected to a series of pattern recognition ability test (PRAT) and judging performance evaluation tasks. The initial results of the first study using ANOVA analyses showed that there were significant differences between the level of expertise for the pattern recognition ability of each of the four body movement groups (jumps, balances, pivots and flexibilities) but results of the 3 X 4 (Expertise X Movement Series) MANOVA indicated no significant main effects [Pillai’s trace = 0.45, F (8, 50) = 1.81, p > 0.05]. However, for their judging performance, ANOVA analyses showed that there were significant differences between the level of expertise for the pattern recognition ability of each of the five apparatus (rope, hoop, ball, clubs and ribbon). The results of the 3 X 5 (Expertise X Apparatus) MANOVA indicated there were significant main effects [Pillai’s trace = 0. 79, F (10, 48) = 3.10, p < 0.05]. This finding was confirmed with a univariate ANOVA. Significant effects were observed for all components of the evaluation exercise as well as for the total (p < 0.05). Post-hoc comparisons revealed that there were significant differences between the experts and non-experts with the novices but there were no differences between the experts with the non-expert participants in their judging performance. However, when the participants were regrouped according to their movement pattern recognition ability; low, average and high, the results showed that there were very significant differences in the judging performances of the three groups classified according to their movement pattern recognition ability [F (2, 27) = 127.55, p = 0.00, w = 0.93]. In the second study, a selected group of non-expert judges had undergone a series of pattern recognition training for three weeks as treatment. The results of the main effects revealed that there were significant differences between the two groups of treatment and non-treatment participants on the PRAT scores [Pillai’s trace = 0. 93, F (1, 8) = 9.81, p < 0.05, ηp2 = 0.93]. This finding was confirmed with a univariate ANOVA. Significant effects were observed for all components of the PRAT as well as for the total (p < 0.05). A post-hoc test (Scheffe) verified that the treatment participants were improving significantly more than the non-treatment participants. As for the judging performance, the results of the main effects revealed that there were no significant differences between the two groups of treatment and non-treatment participants on the judging performance scores [Pillai’s trace = 0. 82, F (5, 4) = 3.60, p > 0.05]. However, univariate analyses revealed that there were significant effects to the judging performance of the ball [F (1, 8) = 5.89, p < 0.05] and clubs routines [F (1, 8) = 7.21, p < 0.05]. The data collected partially support the proposition that pattern recognition ability training will bring a significant improvement particularly in the judging performance of ball and clubs routines which have a dominance of the balance difficulties. These findings confirmed that pattern recognition ability was an important characteristic of the expertise of the rhythmic gymnastics judges. Besides, the findings gives hope that pattern recognition ability could be trained in order to contribute further to the advancement of the expertise of rhythmic gymnastics judges in their judging performance.